PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING KONTEKS BUDAYA BENGKULU TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA SMPI AL-AZHAR 52 KOTA BENGKULU - Mutiasari, Fitria; Susanta, Agus; Muchlis, Effie Efrida (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to see the influence of the Bengkulu Cultural Context Problem Based Learning learning model on the Mathematical Literacy Ability of Students at SMPI Al-Azhar 52 Bengkulu City. The research method used in this research is the analytical method. The sampling technique uses purposive sampling technique. The instrument for collecting data in this research was a mathematical literacy ability test. The test was carried out on Quadrilaterals and Triangles material. Next, analysis of all data is carried out using the following steps: prerequisite test and hypothesis test. The results of the research show a sig value (2-tailed) = 0.044 < significant level (α) = 0.05, so it can be concluded that there is an influence of the Problem Based Learning learning model in the cultural context of Bengkulu on the mathematical literacy abilities of students at SMPI Al-Azhar 52 Kota Bengkulu